Are Nocturnal Hypoxemia and Hypercapnia Associated With Desaturation Immediately After Adenotonsillectomy? - Dalesio, Nicholas M. (Paediatr Anaesth, 2015)
BACKGROUND: Children who undergo adenotonsillectomy for sleep-disordered breathing frequently have postoperative oxygen desaturations. Nocturnal hypoxia has been shown to predict post-operative respiratory complications, however, other gas exchange abnormalities detected on polysomnography (PSG) have not been evaluated. AIM: We sought to determine whether hypercarbia seen on preoperative nocturnal PSG can predict postoperative hypoxemia. METHODS: We conducted a retrospective review of 319 children who underwent polysomnography before adenotonsillectomy. Saturation levels were recorded for at least 2 hours postoperatively, and the primary outcome was desaturation (<90%). RESULTS: The median patient age was 5 years (range, 5 months-17 years). Patients who desaturated postoperatively had higher median peak end-tidal CO(2) (EtCO(2)) levels (55.5 vs. 52 mmHg; P=0.02), lower saturation nadirs (80.5% vs. 88%; P=0.048), and were younger (2 vs. 6 years; P<0.001) than those without desaturation. Age was significantly correlated with peak EtCO(2) (r= −0.16), respiratory disturbance index (RDI; r= −0.23), and oxygen saturation nadir (r= 0.25; all P<0.01). In unadjusted analysis, age<3 years compared to ≥9 years (odds ratio [OR]=10.09; 95% confidence interval [CI]=2.13–96.26), peak EtCO(2)>55 mmHg (OR=3.38; 95% CI=1.21–9.47), and RDI≥10 (OR=2.89; 95% CI=1.05–8.42) were associated with increased odds of desaturation. Multivariable logistic regression on age, race, sex, peak EtCO(2), RDI, opioid use, and saturation nadir showed that only age was significantly associated with postoperative desaturation. Patients 0–2 years old were 10.43 (95% CI=1.89–110.9) times more likely to have desaturation than patients 9–17 years old. CONCLUSION: Patients less than 3 years of age are most likely to have postoperative hypoxemia after adenotonsillectomy. Gas exchange abnormalities did not correlate with postoperative desaturations, although age and peak EtCO(2) did strongly correlate.